'n Samevatting en kritiese evaluasie van B. S. Childs se kanoniese benadering - Van Rensburg, N. A. Janse (Verbum et ecclesia, 1988)
A summary and critical evaluation of B. S. Childs' canonical approach Childs is disappointed with the results of the historical critical method. He made an appeal for a totally new approach in which the relation between historical critical study of the Bible and its theological use as religious literature within the community of faith will be completely rethought. He proposes a canonical approach in which the final form of the text, not the pre- or past-canonical developments, will be normative for the community of faith. Because of Childs' enormous influence as Old Testament interpreter and the high standard of his work in the past, expectations ran high for the publication of his Old Testament Theology. In the light of his bold influence and the enormous promise of his work, Old Testament Theology in a canonical context is unfortunately a disappointment. One can only hope that he still intends writing a book that will illustrate how a theology is written in canonical context.